Platform-Based Management and Psychological Contract Dynamics in Digital Employment: A Systematic Literature Review - Rohani Lestari Napitupulu; Hermin Sirait; Mety Titin Herawaty (FEBI IAIN Langsa, 2026)
The rapid growth of the platform economy has transformed employment relationships through algorithmic management systems that replace human supervision with automated computational controls. While these systems optimize operational efficiency, their impact on worker psychological contracts and social exchange dynamics remains fragmented in existing literature. This systematic literature review synthesizes empirical evidence from 39 studies retrieved from the Scopus database using the PRISMA protocol and PEO framework to examine how platform-based management influences psychological contract formation, fulfillment, and reciprocity in digital work. Methodological quality was evaluated using the Mixed Methods Appraisal Tool (MMAT), and data were analyzed via a six-phase thematic coding procedure. Findings reveal three primary pathways of influence: asymmetry in contract formation driven by automated onboarding, contract fulfillment contingency dictated by perceived algorithmic justice and transparency, and structural reciprocity deficits stemming from a dominant transactional orientation. Furthermore, institutional trust, perceived fairness, and experienced autonomy function as critical cognitive mediators, while platform type and worker dependence moderate behavioral outcomes. Theoretically, this review advances Psychological Contract Theory and Social Exchange Theory by revising foundational assumptions regarding mutuality, agency, and relational investment, while conceptualizing three novel constructs: Algorithmic Reciprocity, Conditional Reciprocity, and Multi-Dimensional Algorithmic Justice. Practically, the study offers targeted guidelines for platform companies, workers, policymakers, and regulators to build equitable digital employment ecosystems.